Behavior analysis of taekwondo athletes according to the rounds of the championship - Menescardi, C.; Estevan, I.; Lopez-Lopez, J. A.; Falcó, C. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to analyse the technical and tactical behaviour of taekwondo athletes in a university level taekwondo championship according to the round. A total of 169 matches, consisting of 1088 performances were videotaped. The results showed that athletes when compete in a final and semifinal round performed more direct actions, simultaneous counterattacks, linear kicks, actions to the chest, and with left leg than when competing in prior rounds, whose technical-tactical behavior is characterized by perform more anticipatory actions than competitors in the final and semifinals. This information serves to focus taekwondo training in direct attacks to the chest and perform simultaneous counterattacks, imitating the final round competitors` behavior.